2014
DOI: 10.1037/sgd0000050
|View full text |Cite
|
Sign up to set email alerts
|

Marital status, gender, and sexual orientation: Implications for employment hiring decisions.

Abstract: Marital status and sexual orientation discrimination has been largely underresearched and has not been researched using working professionals, or with the incorporation of sexual orientation, marital status, and gender interactions. Additionally, with the growing acceptance of same-sex relationships, marriages, and partnerships, the interaction of marital status (i.e., applicants with or without a spouse) and sexual orientation bias in the workplace needs to be examined. Our study used an experimental design t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
0
16
0
2
Order By: Relevance
“…The participants were generally asked to evaluate whether presented résumés match requirements of a given job. Nadler and Kufahl (2014) additionally provided the participants with a video of a fictional job interview. Gorsuch (2014) presented the study as a real job task so the subjects were not aware that they were taking part in an experiment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants were generally asked to evaluate whether presented résumés match requirements of a given job. Nadler and Kufahl (2014) additionally provided the participants with a video of a fictional job interview. Gorsuch (2014) presented the study as a real job task so the subjects were not aware that they were taking part in an experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Most male (female)-dominated occupations also involve (and require) employee traits that are stereotypically associated with males (females) (Weichselbaumer, 2004). Stereotyping may play an important role in an interviewer's approach toward a job applicant (Nadler & Kufahl, 2014); for example, by formulation of stereotype-affirming questions and in formation of final judgments that affect hiring decisions. Job applicants who (stereotypically) violate the gender role required for the job may be sorted away.…”
Section: H4mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is evidence that there exists an interaction effect between sexual orientation and gender during the hiring process. In an interview simulation study, Nadler and Kufahl (2014) reported that sexual minority men received significantly lower hiring scores than sexual minority women who disclosed their identities during a mock interview. Relatedly, sexual minority men are more likely to be discriminated from jobs that are stereotypically oriented toward heterosexual males (Ahmad et al, 2013;Tilcsik, 2011) Present Study Glover, Corrigan, and Wilkniss (2010) indicated that future studies should continue to investigate the role of intersecting contextual variables on employment hiring bias.…”
mentioning
confidence: 99%
“…Marital status is still inquired about on application form, as well as in job interviews [19,20,21]. It has become a norm for employer to check on applicant's marital status and asking such questions before employment.…”
mentioning
confidence: 99%